Implementation and Analysis of NAT and PAT Techniques in Cisco-Based Networks for Efficient IPv4 - abudaber, tasneem; Nuredin Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2026)
Advancements on the Internet lead to a shortage of available IPV4 addresses. The main long-term solution to the IP address scalability problem was to increase the size of the IP address. This study focuses on NAT and PAT that were applied in a controlled network using Cisco devices. A private Local Area Network (LAN) was set up with the address 192.168.0.0/16, which was then connected to a limited range of public IP addresses (203.0.113.0/30). The NAT and PAT techniques were applied to examine connectivity between internal and external devices, and address translation was verified using Cisco IOS commands. The Nat terminology and all configurations were implemented using the Cisco Packet Tracer simulation tool. The results demonstrate how NAT can help manage the limited availability of IP addresses, making it easier to scale networks. Furthermore, the study examined the operational behavior of NAT and its role in addressing challenges related to IPv4 address scarcity. In this paper, we will stimulate the network address translation and port address translation routing technique.